Військово-організаційна діяльність ОУН у 1929–1939 рр.: (документознавчий аспект) - Лісіна, Світлана Омелянівна (Національний університет "Львівська політехніка", 2008)
Дисертація присвячена комплексному документознавчому дослідженню військово-організаційної діяльності ОУН у 1929-1939 рр. Відтворено процес підготовки та стан функціонування офіційних документів Організації з військових питань міжвоєнного десятиліття. Проаналізовано вишкільну діяльність Організації, формування старшинського складу та стан військової підготовки членів Організації. Досліджено військову діяльність ОУН в організуванні збройної сили Карпатської України, націоналістичних збройних формувань. Здійснено опрацювання військово-теоретичних праць чільних діячів ОУН та подано аналіз їх воєнної доктрини напередодні Другої світової війни. Опрацьовано націоналістичні періодичні видання та їх публікації з військових питань, як джерельну базу військово-організаційної діяльності ОУН. Диссертация посвящена комплексному документоведческому исследованию военно-организационной деятельности ОУН в 1929-1939 гг. Воспроизведен процесс подготовки и функционирования официальных документов Организации по военным вопросам межвоенного десятилетия. Проанализирована деятельность Организации по выучке кадров, формированию старшинского состава и состоянию военной подготовки членов ОУН. Исследовано военную деятельность ОУН по организации вооруженных сил Карпатской Украины, националистических вооруженных формирований. Осуществлен анализ основных военно-теоретических трудов деятелей ОУН и дано характеристику их военной доктрины в канун Второй мировой войны. Проанализированы националистические периодические издания и их публикации по военным вопросам как источник информации о военно-организационной деятельности ОУН. Dissertation is devoted to the complex research of military-organizational activity of OUN in 1929-1939. The historiography analysis of literature, which is devoted to the research of military-organizational aspects of activity of OUN, was carried out. The analysis of document inheritance of Ukrainian Nationalists Organization on the basis of official records characterizes their military-organizational activity and confirms the globalness of organization and the possibility of its activity at state level. Military teaching, the purpose of which was training of personnels for the forecasted military conflict, was examined on the basis of the proper documents and concrete system. Moreover, there was studied the personalias of militay men: E. Konovalec, M. Kapustyanskiy, V. Kurmanovich, R. Sushko, R. Yariy, O. Hasyn, M. Kolodzinskiy, Z. Kossak and others, there was also considered their creative scientific and publicism revisions; it was looked at theoretical bases of military doctrine forming in the eve of Second World War, which didn’t lose its value and is important nowadays for alteration of modern Ukraine and reformation of Military Powers, and its two conceptions; furthermore, the basic labours of OUN main figures from OUN military reviewers are analysed. In the thesis there was exposed the place and role of OUN magazines, which represented and fixed historical period with all its most characteristic pecularities and socio-economic features. Abovementioned OUN magazines were the considerable informative adding to the system of introduction of soldiery and organizational postulates of Organization. The magazines “Surma” and “Rozbudova nacij” with the appropriation of the name of press organs of PUN were taken to official editions of OUN. For implementation of PUN’s tasks on nationalistic ideas propaganda in the country under the control of OUN on ZUZ a number of editions were created (“Ukrainskiy holos”, ”Studentskiy shlyach”, “Nash klych”, “Probojem”, “Studentskiy visnyk”, “Yunacka dumka”, “Hotovi”, “Molodi druzi”, “Probij”, “Byuleten Krayovoyi Ekzekutyvy OUN”, “Yunak”, “Yunactvo” and other), which gave the themes of national consciousness, spirit, idea, heroism, central publications and oriented young people on a fight for national ideals. The decades of subsequent fight after war termination on Western Ukrainian Land gave a shove to continuation of national liberation competitions with other methods, in other terms. It resulted in the formation of Independent Ukrainian State at the end of XX century on the ethnic Ukrainian Land, and that was what the Ukrainian nationalists fought for.
Военно-организационная деятельность ОУН в 1929–1939 гг.: (документоведческий аспект)
Military-organizational activity of OUN in 1929–1939: (dokumentarity aspect)
Keywords: Організація Українських Націоналістів; військово-організаційна діяльність; вишкіл; збройні формування; офіційні документи; військово-теоретичні праці; націоналістична періодика; Организация Украинских Националистов; военно-организационная деятельность; выучка; вооруженные формирования; официальные документы; военно-теоретические труды; националистическая периодика; Organization of Ukrainian Nationalists; military-organizational activity; teaching; military powers; official documents; theoretical labours; nationalistic periodicals